Interactions of olomoucine II with human liver microsomal cytochromes P450 - Siller, Michal; Anzenbacher, Pavel; Anzenbacherova, Eva; Dolezal, Karel; Popa, Igor; Strnad, Miroslav (Drug metabolism and disposition: the biological fate of chemicals, 2009)
Olomoucine II is a cyclin-dependent kinase inhibitor and a potential antineoplastic agent because it can arrest animal cell cycles. This study examines its interactions with human liver microsomal cytochrome P450 (P450) enzymes. Spectroscopic and high-performance liquid chromatography (HPLC) methods were used to estimate the degree of olomoucine II-mediated inhibition of enzymatic activities of eight drug-metabolizing P450s in vitro. In addition, mass spectrometry coupled with HPLC was used to identify an olomoucine II metabolite (2,5-dihydroxyroscovitine) formed in the reaction mixtures, and CYP3A4 was found to be responsible for the hydroxylation of the N(6)-benzyl ring at position 5, leading to this compound. Olomoucine II significantly inhibited the enzymatic activities of CYP1A2, CYP2C9, and (to a lesser degree) CYP3A4. The results indicate that use of olomoucine II as a drug could affect the activities of CYP3A4, CYP1A2, and CYP2C9 in vivo. Hence, the clinical relevance of these interactions should be carefully evaluated.
Keywords: Microsomes, Liver; cytochrom P450 CYP2C9; substrátová specifita; Cytochrome P-450 CYP3A; Cytochrome P-450 CYP2C9; jaterní mikrozomy; lidé; Humans; Oxidoreductases, N-Demethylating; Purines; játra; N-demethylasy; Cytochrome P-450 CYP2B6; Liver; puriny; protinádorové látky; Cyclin-Dependent Kinase Inhibitor Proteins; Antineoplastic Agents; Aryl Hydrocarbon Hydroxylases; Cytochrome P-450 CYP3A Inhibitors; inhibitory cytochromu P450 CYP3A; Substrate Specificity; Cytochrome P-450 Enzyme Inhibitors; aromatické hydroxylasy; vysokoúčinná kapalinová chromatografie; inhibitory cytochromu P450; Cytochrome P-450 CYP1A2 Inhibitors; Drug Interactions; cytochrom P-450 CYP3A; lékové interakce; inhibiční proteiny cyklin-dependentních kinas; Chromatography, High Pressure Liquid; inhibitory cytochromu P450 CYP1A2; cytochrom P450 CYP2B6